2011
DOI: 10.1142/s1793604711002226
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Synthesis and Modification for Iron Phosphate

Abstract: In order to improve the electrochemical performance of FePO 4, the method of Cr 3+ ion-doped FePO 4 was proposed in this paper. FePO 4 and doped Fe 1-x Cr x PO 4 (x = 0.02,0.04,0.06 and 0.08) were prepared by homogeneous co-precipitation followed by spray drying method, and then the samples were sintered at different temperatures (380°C, 460°C, 550°C and 650°C). Physical-chemical properties were characterized by using thermogravimetric analysis (TG), X-ray diffraction (XRD) and scanning electron microscope (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…To overcome these shortcomings, cation doping is usually an effective method to improve the electronic and ionic conductivity. 21,22 Unfortunately, carbon coating is not suitable to improve the electrochemical performance of FePO 4 because of easy reduction from Fe 3+ to Fe 2+ when adding carbon sources under 460 C heat treatment. 23,24 Since graphene was rst prepared by mechanical exfoliation and chemical vapour deposition, this material has attracted huge interest, owing to its large surface area, high electronic conductivity and excellent chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these shortcomings, cation doping is usually an effective method to improve the electronic and ionic conductivity. 21,22 Unfortunately, carbon coating is not suitable to improve the electrochemical performance of FePO 4 because of easy reduction from Fe 3+ to Fe 2+ when adding carbon sources under 460 C heat treatment. 23,24 Since graphene was rst prepared by mechanical exfoliation and chemical vapour deposition, this material has attracted huge interest, owing to its large surface area, high electronic conductivity and excellent chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [17] obtained amorphous mesoporous FePO 4 by a template method, which was then used as cathode material. X. Yang et al [18] found that the Cr 3+ ion-doped FePO 4 (Fe 1−x Cr x PO 4 ) could effectively improve electrochemical performance overall.…”
Section: Introductionmentioning
confidence: 99%
“…Spray drying is a high throughput, large scale unit operation that desiccates powders economically. Since 1994, as many as 50 articles indexed by WoS mention spray drying in combination with sol‐gel synthesis, carbothermal reduction, solid state reaction, and co‐precipitation . Several studies introduce multiple carbon sources—starch, glucose and oxalic acid, carbon nanotubes, and PVA—then calcine the solids at temperatures as high as 800normalC.…”
Section: Influence Of Atomization Conditions On Spray Drying Lithium mentioning
confidence: 99%